The Influence of the GETAR Spiritual Approach on Smoking Behavior of Junior High School Students in Palu City, Indonesia - Muhammad Ryman Napirah1 , Ridwan Amiruddin2 , Sukri Palutturi3 , Stang4 , Aminuddin Syam5 , Darmawan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Smoking cases at the age of children less than 18 years will have a very fatal impact because consideringthe age of the child who is still growing. GETAR (Movement without Smoking) spiritual approach usesthe concept of religion, which in this case is exemplified by Islam by helping individuals to find theirnature. The purpose of this study is to analyze the effect of the GETAR spiritual approach on smokingbehavior of junior high school students in Palu City, Indonesia. This type of research is a quasy experiment.The sample consisted of 35 smokers in grade 7, 8, and 9 at SMPN 1 Palu as an intervention group, withsaturated sampling technique, as a control group, and 35 students in grade 7, 8, and 9 at SMPN 4 Palu.The data were analysis with paired sample t test and independent sample t test. This study showed thatthere are differences in knowledge (p = 0,000), attitudes (p = 0,000), and actions (p = 0,000) students ofSMPN 1 Palu about smoking before and after GETAR spiritual intervention. And there are differences inthe knowledge (p = 0,000), attitudes (p = 0.020), and actions (p = 0,000) between students who were givenGETAR spiritual intervention (students of SMPN 1 Palu) and those who were not given GETAR spiritualintervention (students of SMPN 4 Palu). It concludes that there is a difference in the knowledge, attitudes,and actions of SMPN 1 Palu students about smoking before and after the spiritual intervention of GETAR.And there is a difference in the knowledge, attitudes, and actions of students between those who were giventhe spiritual intervention of GETAR (students of SMPN 1 Palu) and those who were not given the spiritualintervention of GETAR (students of SMPN 4 Palu).